MENINGKATKAN KEMAMPUAN LITERASI GURU SMA NEGERI 1 LIMBANGAN MELALUI FGD PENULISAN KARYA ILMIAH (CHAPTER BOOK) - Retno Anggoro; Khaeroman; Fitri Suprapti; Erwin Sutantyo (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2023)
In carrying out of duties as a teacher, in addition to teaching, a teacher also required to be able to make a good scientific work. Writing ability is one of main subject of the teacher when purpose a scientific work. But the reality, still faced some teachers that minus of ability on purpose a good scientific work. Using the latest version of application technology that improved purposes scientific work progress not fully handle as well by teachers on SMA N 1 Limbangan is one of issue for the present time. FGD (Focus Discussion Group) that doing by polimarin lectures and SMA N 1 Limbangan teachers expected can improve kowladge and ability of the teachers on literature skill and purposing scientific work (chapter book) as an obbilgation of the teachers on SMA N 1 Limbangan. The result of FGD is given knowledge and skill for the teachers for using Mendeley application as a tool for citation a reference. Aside from that given knowledge and skill for the teachers abaout paraphrase of the words, its have benefite for teacher for purposing scintifics work without doing plagiarism. And the last is given knowledge and skill about using application of electronic information system called SCI hub for downloading some journal as a reference for purposing scientific work for free.